Social Media Optimization in the Young Small Medium Enterprise (Journal of Entrepreneurship, Management and Industry (JEMI), 2022)
Recently, this is an era in which social media has been widely used as a communication channel, specifically by certain parties in building their business and promoting their products through the dissemination of existing content. Almost all companies now have social media that post new innovations in the form of new products or services, as well as company activities carried out. Small Medium Enterprises (SMEs) continue to be aggressive with marketing as one thing that can be done is social media marketing through social media. Entrepreneurs have started to look at how to market their products online, but in practice it is still not optimal. Entrepreneurs still have other problems, one of which is the visual technique they have to show when they want to share product photos or videos, it must be attractive and have good competitiveness on social media. To create a good image and attract attention and product competitiveness, entrepreneurs must be creative and innovative in creating products. An attractive product is a different from products already on the market. Currently, there are many entrepreneurs who do marketing through social media. However, most young entrepreneurs only focus on selling without thinking about the quality of their marketing communication strategy. With the quality of good marketing communications, a product will be easier for the audience to remember. So the opportunity to increase sales results are even greater.